Photo-, thermo- and optically stimulated luminescence of monoclinic zirconia - Kiisk, Valter; Puust, Laurits; Utt, Kathriin; Maaroos, Aarne; Mändar, Hugo; Viviani, Erica; Piccinelli, Fabio; Saar, Rando; Joost, Urmas; Sildos, Ilmo (Journal of luminescence, 2016)
We carried out a careful photoluminescence (PL) and thermoluminescence (TL) characterization of nominally pure monoclinic ZrO2 nanopowders subject to oxidative vs reductive annealing (up to 1450°C). The two kinds of studied zirconia (sol-gel-prepared vs commercial powder) exhibited virtually identical 490nm PL emission band and 280nm PL excitation band with slight, but clearly detectable variations in the spectral shape. The TL glow peaks, recorded over the temperature range −100 to 300°C, showed an interplay depending on the type and treatment of sample. There is a strong evidence that the −35 and 205°C glow peaks are due to oxygen vacancies whereas the 5°C glow peak may relate to oxygen interstitials and the 110°C glow peak to surface defects. Although a number of distinct glow peaks emerge, the material still seems to contain a quasi-continuous distribution of trap depths. In comparison to TL, we also demonstrate effective optically stimulated luminescence (OSL) from this polymorph of ZrO2 under red and NIR illumination at ~1W/cm2. All traps responsible for the principal TL peaks were also found to be OSL-active, which widens the applied importance of the material.